Von Willebrand Factor as a new marker for non‐invasive assessment of liver fibrosis and cirrhosis in patients with chronic hepatitis C. Issue 3 (5th December 2013) - Maieron, A.; Salzl, P.; Peck‐Radosavljevic, M.; Trauner, M.; Hametner, S.; Schöfl, R.; Ferenci, P.; Ferlitsch, M.
Summary Background Staging of liver fibrosis in patients with chronic hepatitis C (CHC) is recommended prior to anti‐viral therapy. As vWF‐Ag was shown as a predictor of portal hypertension, decompensation and mortality in patients with liver cirrhosis, we performed this study to investigate if vWF‐Ag is able to predict different fibrosis stages and if it is comparable to other fibrosis scores. Aim To investigate if vWF‐Ag is able to predict different fibrosis stages and if it is comparable to other fibrosis scores. Methods We analysed 294 patients with chronic hepatitis C who underwent biopsy. We assessed stage of liver fibrosis according to Metavir, measured vWF‐Ag and calculated different fibrosis scores (APRI, FCI, FORNS, FI, Fib‐4) and compared them by AUCs. We also calculated a new score: vWF‐Ag/thrombocytes (VITRO score) for prediction of fibrosis. Results vWF‐Ag levels were increasing with stage of fibrosis: F0: vWF‐Ag was median 136.5%, FI 140.6%, FII 157.5%, FIII 171.0%, FIV 252.0%; P < 0.001. vWF‐Ag and VITRO score produced AUCs of 0.7 and 0.72 for ≥F2, comparable to the AUCs of APRI, Fib‐4, FORNS with 0.75, 0.65 and 0.64 (P > 0.05). For ≥F3 AUCs were 0.79 and 0.86 for vWF‐Ag and VITRO score, comparable with AUCs of 0.79, 0.86 and 0.87 for APRI, Fib‐4 and FORNS. Cirrhosis shows AUCs of 0.84 and 0.89 for vWF‐Ag and VITRO score, APRI, Fib‐4 and FORNS showed similar results with AUCs of 0.82, 0.88 and 0.87. Conclusions vWF‐Ag and VITRO score offer an easy possibility to evaluate the stage of fibrosis to diagnose subclinical cirrhosis in patients with chronic hepatitis C. Both vWF‐Ag and VITRO score show equal performance in comparison to other fibrosis scores assessed in our study.